Conjugation of LasR Quorum-Sensing Inhibitors with Ciprofloxacin Decreases the Antibiotic Tolerance of P. aeruginosa Clinical Strains - Daria Bortolotti; Claudio Trapella; Alessandra Bragonzi; Paolo Marchetti; Vinicio Zanirato; Andrea Alogna; Valentina Gentili; Carlo Cervellati; Giuseppe Valacchi; Mariangela Sicolo; Giulia Turrin; Anna Fantinati; et al. (Journal of Chemistry)
Pseudomonas aeruginosa is a Gram-negative bacterium that commonly infects subjects with weakened immune system causing deadly infections above all at pulmonary level. During infection, P. aeruginosa produces a well-organized bacterial structure, called biofilm, activating the quorum-sensing (QS) signaling, a mechanism of gene regulation. In this work, we synthesized already known QS inhibitors (QSi) designed on the scaffold of the N-(3-oxododecanoyl) homoserine lactone (3O-C12-HSL) QS molecule and conjugated them with ciprofloxacin to inhibit P. aeruginosa biofilm formation and increase the antibiotic susceptibility of clinical strains. We identified, for the first time, a QSi conjugated with ciprofloxacin (ET37), that is able to reduce the formation of biofilm and the onset of tolerant clones in P. aeruginosa clinical strains. This compound could have a wide application in clinical setting. The possibility to affect biofilm formation in chronically infected patients, such as patients affected by cystic fibrosis, and to reduce the onset of ciprofloxacin resistance would improve patient healing and allow to decrease antibiotic drug dosage.